Melt Processed PCL/PEG Scaffold With Discrete Pore Size Gradient for Selective Cellular Infiltration. Issue 2 (7th October 2015) - Scaffaro, Roberto; Lopresti, Francesco; Botta, Luigi; Rigogliuso, Salvatrice; Ghersi, Giulio
Abstract : In order to develop scaffold able to mimic the natural gradient properties of tissues, biphasic and triphasic approaches were adopted. In this work, polycaprolactone/polyethylene glycol (PCL/PEG) scaffolds were prepared by using a combination of melt mixing and selective leaching without harmful solvents. The method permitted to develop three‐layer scaffolds with high control of porosity and pore size. The mechanical properties were evaluated under physiological condition in order to simulate the real conditions of work. Co‐culture of osteoblastic and fibroblastic mice cells were carried out in order to study the differential cellular permeation through the different pore size layers. Abstract : In this work, the authors developed a three‐layered PCL scaffold through a melt mixing–compression molding–particle leaching process. The pore size is well controlled by NaCl particles dimension. The mechanical properties and cell migration capability of the scaffold is significantly impacted by the pore size.